Therapeutic use of the HPV vaccine in Recurrent Respiratory Papillomatosis: A case report. (February 2017) - Sullivan, Christopher; Curtis, Stuart; Mouzakes, Jason
Abstract: Recurrent Respiratory Papillomatosis (RRP) is a condition characterized by recurring squamous papillomas in the aerodigestive tract due to Human Papilloma Virus (HPV) infection. Treatment includes surgical debridement of the lesions often with adjuvant therapy. A newer adjuvant agent being tested is the HPV vaccine. The case report includes a child with RRP who underwent 10 surgeries in a year with an average inter-surgical interval (ISI) of 46 days. The patient then received the scheduled regimen of 3 doses of 9 valent HPV vaccine. Since beginning the vaccination, her average ISI increased to 113 days and as of writing of this paper only 1 surgery in the last 340 days. It is theorized that the increase in humoral response to the virus can slow the course of the disease, lengthen the ISI, and decrease morbidity. The results of this case report lends evidence to the use of the HPV vaccine as a therapeutic adjuvant therapy for RRP.